Antioxidant Activity Of Effervescent Granule Of Red Dragon Fruit Peel Extract (Hylocereus Polyrhizus W.) Using The DPPH Method - Toding, Ficanata Adhiguna; Niluh Puspita Dewi; Dermiati T; Shinta Widya Wulandari (Sean Institute, 2024)
Red Dragon Fruit Peel (Hylocereus polyrhizus W.) contains chemicals such as alkaloids, flavonoids, saponins, phenols, and steroids. Flavonoids and phenols are compounds that have antioxidant properties. Red Dragon Fruit Peel extract is formulated in effervescent granule dosage form with different concentrations of 0%, 20%, 25%, and 30% based on its antioxidant activity. The purpose of this study was to determine the effect of concentration differences on the antioxidant activity of effervescent granules produced. The research method uses a completely randomized design (CRD) which includes sampling, sample processing, phytochemical testing, extract preparation, effervescent granule preparation, effervescent granule physical quality testing, effervescent granule testing, antioxidant activity testing, and data analysis. Data from physical quality testing and the IC50 value of effervescent granules were analyzed descriptively using the Analysis of Variance (ANOVA) method with a 95% confidence level. The results obtained show that Red Dragon Fruit Peel extract can be formulated into effervescent granules, and the physical quality test results meet the physical quality requirements for all concentrations. The effervescent granule formulations produced at all concentrations have a very strong antioxidant effect (<50 ppm). The variation of Red Dragon Fruit Peel extract concentration in effervescent granule formulation has a significant effect on its antioxidant activity